2019
DOI: 10.1063/1.5093639
|View full text |Cite
|
Sign up to set email alerts
|

Laser-driven semiconductor switch for generating nanosecond pulses from a megawatt gyrotron

Abstract: A laser-driven semiconductor switch (LDSS) employing silicon (Si) and gallium arsenide (GaAs) wafers has been used to produce nanosecond-scale pulses from a 3 ls, 110 GHz gyrotron at the megawatt power level. Photoconductivity was induced in the wafers using a 532 nm laser, which produced 6 ns, 230 mJ pulses. Irradiation of a single Si wafer by the laser produced 110 GHz RF pulses with a 9 ns width and >70% reflectance. Under the same conditions, a single GaAs wafer yielded 24 ns 110 GHz RF pulses with >78% re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…The required microwave power for this application is however in the megawatt range and the frequency requirements are below those for the DNP-NMR application [14,15]. Other applications have also emerged in the past two decades where the required power is in the range of tens of watts to a few tens of kWs [16][17][18][19][20][21][22][23][24][25]. A major application which has pushed the development of gyrotrons in the THz range is DNP-NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The required microwave power for this application is however in the megawatt range and the frequency requirements are below those for the DNP-NMR application [14,15]. Other applications have also emerged in the past two decades where the required power is in the range of tens of watts to a few tens of kWs [16][17][18][19][20][21][22][23][24][25]. A major application which has pushed the development of gyrotrons in the THz range is DNP-NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The modularity of the tube has allowed for the study of components relevant to highpower gyrotron for plasma heating, such as a single-stage depressed collector [18], a smooth mirror mode converter [19], and a new cavity capable of producing radiation at 110 GHz or 124 GHz [20]. It has also been used extensively for various applications, including dielectric multipactor measurements [21], gas breakdown studies [22] and is currently used as a source for testing an externally driven particle accelerator structure [23,24]. Recently, the gyrotron has been modified by installing an internal mode converter that couples the rf to a corrugated waveguide inside the gyrotron.…”
Section: Methodsmentioning
confidence: 99%
“…As demonstrated in earlier studies (e.g., [16], [20], [22]), the electromagnetic (EM) behavior of optically activated semiconductors may be accurately modeled via the spatiotemporal calculation of the electron and hole densities, which can then be used to calculate the spatiotemporal complex permittivity via a Drude approximation. The model employed in this study is identical to these earlier works, with the exception that these calculations are generalized to three dimensions and solved using the commercial multiphysics software, COMSOL.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Notably, Ren et al [13] demonstrated an in-waveguide PC attenuator at 170-260 GHz, capable of 60 dB attenuation; however, the transient performance of many of these devices has not been reported. Switching of microwave, millimeterwave, and THz radiation using PC devices in quasi-optical and other configurations has been a focus of research for decades and remains a topic of study [14]- [20]. In these studies, PC devices have demonstrated switching times ranging from a few nanoseconds to tens of microseconds, suggesting that PC devices are able to satisfy the switching time requirements of this application.…”
Section: Introductionmentioning
confidence: 99%